1994
DOI: 10.1002/eji.1830241227
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocyte‐mediated antiviral immune responses in mice are diminished by treatment with monoclonal antibody directed against the interleukin‐2 receptor

Abstract: Blocking the interleukin-2 receptor's alpha-chain in lymphocytic choriomeningitis virus-infected mice by treatment with monoclonal antibodies diminished the increase of numbers of CD8+ T lymphocytes in spleens and prevented CD8+ T lymphocyte-mediated virus clearance from organs as well as generation of virus-specific cytotoxic T lymphocytes. Also, the CD8+ T cell-mediated early phase of the delayed-type hypersensitivity footpad swelling reaction was decreased. The same treatment had no effect on the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Given the ability of IL-2 to regulate antiviral T cell responses (11,24), it is curious that during the early phase of antiviral CD4 cell response paracrine IL-2 signaling operates efficiently while autocrine signaling is difficult to detect. Because IL-2 can promote apoptosis of activated T cells (25), the intensity of STAT5 activation that autocrine IL-2 signaling might elicit could necessitate that IL-2-expressing CD4 cells become refractory to STAT5 activation to limit apoptosis (or perhaps other deleterious effects).…”
Section: Resultsmentioning
confidence: 99%
“…Given the ability of IL-2 to regulate antiviral T cell responses (11,24), it is curious that during the early phase of antiviral CD4 cell response paracrine IL-2 signaling operates efficiently while autocrine signaling is difficult to detect. Because IL-2 can promote apoptosis of activated T cells (25), the intensity of STAT5 activation that autocrine IL-2 signaling might elicit could necessitate that IL-2-expressing CD4 cells become refractory to STAT5 activation to limit apoptosis (or perhaps other deleterious effects).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, our results revealed a heretofore unappreciated dichotomy in the role of IL-2 in regulating the growth and death of primary antiviral CD8 T cells in nonlymphoid tissues. There are limited data available on the role of IL-2 in antiviral CD8 T cell responses in vivo, and the findings are inconsistent (25)(26)(27). The reasons for these discrepancies are unclear, but Ag-specific CD8 T cells were not rigorously quantitated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the role of IL-2 in CD8 T cell responses to virus infections, only the responses to lymphocytic choriomeningitis virus and vaccinia virus infections have been studied. In one case the response to both of these infections was largely IL-2 independent (25), while in two other studies, which assessed the total increase in splenic CD8 T cell number during lymphocytic choriomeningitis virus infection, a lack of endogenous IL-2 severely inhibited the expansion of CD8 T cells (26,27). Regarding the contraction phase of antiviral T cell responses, cytokine deprivation has been proposed to be responsible for the loss of activated T cells (28 -30); therefore, cell death may be attributed to the withdrawal of growth factors such as IL-2.…”
mentioning
confidence: 99%
“…Administration of these cytokines has been shown to augment the CD8 response in the context of a range of immunization protocols (19 -24). Furthermore, experiments in which the activity of IL-2 or IL-15 has been blocked have suggested that their endogenous production contributes to the generation of CD8 responses during infection with some viruses or in the induction of delayed-type hypersensitivity (25)(26)(27)(28)(29); DC were found to be the crucial source of IL-15 in the latter setting (29). Notably, however, analysis of CD8 ϩ T cell responses in some other models has failed to show a requirement for IL-2 or IL-15, indicating that distinct mechanisms can drive CD8 responses under different conditions of immunization/infection (30 -32).…”
Section: Ross-priming Is a Process By Which Functional Cd8mentioning
confidence: 99%
“…ϩ T cell responses during certain viral infections (25)(26)(27)(28), these cytokines seemed plausible candidates as downstream mediators of IFN-␣ during cross-priming. To evaluate potential differences in responsiveness to IL-2 and IL-15, the kinetics of expression of IL-2R and IL-15R subunits on the surface of OT-I cells in mice immunized with OVA or OVA ϩ IFN-␣ was analyzed (Fig.…”
Section: Il-15 Contribute To the Generation Of Cd8mentioning
confidence: 99%